Impacts of chronic disease prevention programs implemented by private health insurers: a systematic review - Sithara Wanni Arachchige Dona; Mary Rose Angeles; Natasha Hall; Jennifer J. Watts; Anna Peeters; Martin Hensher (BMC, 2021)
Abstract Background Chronic diseases contribute to a significant proportion (71%) of all deaths each year worldwide. Governments and other stakeholders worldwide have taken various actions to tackle the key risk factors contributing to the prevalence and impact of chronic diseases. Private health insurers (PHI) are one key stakeholders, particularly in Australian health system, and their engagement in chronic disease prevention is growing. Therefore, we investigated the impacts of chronic disease prevention interventions implemented by PHI both in Australia and internationally. Method We searched multiple databases (Business Source Complete, CINAHL, Global Health, Health Business Elite, Medline, PsycINFO, and Scopus) and grey literature for studies/reports published in English until September 2020 using search terms on the impacts of chronic disease prevention interventions delivered by PHIs. Two reviewers assessed the risk of bias using a quality assessment tool developed by Effective Public Healthcare Panacea Project. After data extraction, the literature was synthesised thematically based on the types of the interventions reported across studies. The study protocol was registered in PROSPERO, CRD42020145644. Results Of 7789 records, 29 studies were eligible for inclusion. There were predominantly four types of interventions implemented by PHIs: Financial incentives, health coaching, wellness programs, and group medical appointments. Outcome measures across studies were varied, making it challenging to compare the difference between the effectiveness of different intervention types. Most studies reported that the impacts of interventions, such as increase in healthy eating, physical activity, and lower hospital admissions, last for a shorter term if the length of the intervention is shorter. Interpretation Although it is challenging to conclude which intervention type was the most effective, it appeared that, regardless of the intervention types, PHI interventions of longer duration (at least 2 years) were more beneficial and outcomes were more sustained than those PHI interventions that lasted for a shorter period. Funding Primary source of funding was Geelong Medical and Hospital Benefits Association (GMHBA), an Australian private health insurer.